Governance matters on non-performing loans: Evidence from emerging markets - Burak Büyükoğlu; Ahmet Şit; İbrahim Halil Ekşi (PSL Quarterly Review, 2021)
In this study, new determinants of non-performing loans (NPL) for the MSCI emerging countries were investigated. For this purpose, a new index was formed using the World Bank's Worldwide Governance Indicator data from 2002 to 2018. To test the effect of governance on NPL, we used the GMM technique. As a robustness test for GMM results, we employed the DOLSMG technique. According to the results, NPL was affected negatively by the DOI: governance index. This result could be of interest to policymakers and regulators as a macroprudential policy tool.
Keywords: C51; G21; G2; 330; Non-performing loans; Worldwide Governance Indicators